Location of the Intermediate Echelon to Add Purchase Value and Sustainability Criteria in a Mining Supply Network - Derpich-Contreras, I; Sepulveda-Salas, J; Barraza-Alonso, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This study presents an operational analysis to determine the location of an intermediate hub in a supply network for the mining industry, incorporating sustainability criteria through an optimization model. The sector of small, medium, and artisan mining enterprises (PAMMA), in Chile, has the same pressure as large mining to meet the demands of sustainability in the medium term, but the network of PAMMA facilities is precarious and requires government support for development. One strategy to improve the supply network is to locate intermediate points with limited capacities (called purchasing powers) to help the viability of the business model by incorporating sustainability objectives, such as diminishing the movement of minerals, as well as reducing the carbon footprint and gas emissions, all in support the promotion of the activity of small miners. In order to achieve the strategy above, a mathematical model of location and sustainable capacity is proposed. A grouping of suppliers was carried out to establish the number of mining suppliers in each cluster and the location of the intermediate hubs. Then, the prioritization of the parameters and classification of the processing plant alternatives was performed to define a vector of weights to rank the degree of sustainability. A sustainability matrix was calculated on the basis of the distances and transportation costs between the supplier hubs of the supply network and the processing plants. With each of these factors, a capacity model was developed to validate the mineral process flows in the supply network and estimate the expected productivity levels. The model is intended to support operational decision making when determining the location of an intermediate purchasing power that reduces the impact of transportation costs and emissions. The model was applied in a case study of the supply network in the small mining sector in Chile. The results recommend the location of hubs to add value and encourage investment in the PAMMA supply network. © 2022 by the authors.